Have Fun at the Museum or How to Teach Without Teaching. The Use of The Ludic Techniques in the Polish as a Foreign Language Teaching Lessons Conducted at the Museum Exhibition (Theatralisation, Storytelling, Gamification) - Žák-Caplot, Katarzyna (Ludicity in (Glotto)Didactic, 2020)
When we play, it inspires us to creative activity. Games unite groups of engaged participants and give us the opportunity to express ourselves. At the same time, games allow us to spend a free time pleasantly. Similar goals are set for a modern participatory museum, which wants to create exhibitions, to enter into a dialogue with its recipients and to take into account their historical and cultural experiences. Therefore, it seems natural to conduct museum educational classes based on ludic techniques. The Museum of Warsaw is deeply interested in cooperation with a new group of participants, who are foreigners living in the capital. Their observations and cultural experience will likely make them see Warsaw from a different perspective. However, to cooperate and communicate efficiently a communication channel is needed. For this reason the Museum of Warsaw decided to set up a classes of Polish to foreigners which take place directly at the exhibition. To involve the participants fully a teacher uses a lot of ludic elements like: staging, storytelling or gamification. This article presents the validity of ludic elements in museum and language education. It will also show the methods of their practical application in a language lessons in the Museum of Warsaw.